STRENGTHENING GREEN ENTREPRENEURSHIP AMONG COASTAL MSMES IN KENDARI THROUGH ORGANIC WASTE-BASED PRODUCT INNOVATION AND DIGITAL MARKETING PLATFORMS - Imran, Imran; Rajuddin, Wa Ode Nursaadha; Farih, Muhamad; Asri, Yesi; Lisnawati, Lisnawati (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study aims to analyze the role of green entrepreneurship in strengthening the competitiveness of micro, small, and medium enterprises (MSMEs) in coastal areas through organic waste-based product innovation and the utilization of digital marketing platforms. The research background arises from the growing urgency for sustainable business transformation within the MSME sector, which simultaneously faces environmental, social, and economic pressures. This study employs a quantitative descriptive approach by collecting primary data through questionnaires from 50 coastal MSME actors in Kendari. The data were analyzed using statistical methods to examine the influence of innovative waste utilization, understanding of green entrepreneurship, and digital marketing adoption on the performance and sustainability of MSMEs. The results show that innovative use of organic waste positively impacts the economic value and environmental responsibility of MSMEs, while the integration of digital marketing enhances their market reach and business efficiency. These findings highlight that aligning ecological innovation with digital capabilities significantly contributes to the development of a resilient and sustainable local economy. The main contribution of this study lies in its empirical evidence that connects green entrepreneurship and digital transformation as key drivers of circular economy-based economic empowerment in coastal regions. The novelty of this research lies in the combination of two strategic approaches waste-based innovation and digital marketing in one integrative model to increase the sustainable competitiveness of coastal MSMEs.